Mechanism of N-Acetyl-D-alloisoleucine in Controlling Strawberry Black Root Rot - Jialu Xu; Jianxiu Hao; Mingmin Zhao; Xiaoyu Zhang; Ruixiang Niu; Yiran Li; Zhen Wang; Shuo Zhang; Sumei Zhao; Siran Li; Hongyou Zhou (Plants)
China is the largest strawberry producer in the world. Strawberry black root rot is a novel disease that occurs in Hohhot, Inner Mongolia. In the present study, the inhibitory effects of Bacillus subtilis S-16 and its fermented form on strawberry black root rot caused by Fusarium asiaticum were tested. The inhibition rates were 56.31% and 65.95%, respectively. Furthermore, the metabolic substances were analysed using LC-MS/MS. A total of 68 substances were identified, including 18 amino acids, 7 of which have been reported to have pro-growth and antibacterial functions. Among these seven amino acids, N-acetyl-D-alloisoleucine (NAD) had the strongest inhibitory effect on F. asiaticum. In addition, NAD caused the mycelia of F. asiaticum to appear shrivelled and deformed under electron microscopy. Furthermore, the effect of NAD on F. asiaticum was tested. The results indicate that NAD had a better prevention effect when used with hymexazol. Finally, the fungal biomass of F. asiaticum in strawberry roots was measured at different times using two treatment methods: treating plant roots with NAD and a spore suspension of F. asiaticum concurrently and with F. asiaticum alone. The colonisation response of F. asiaticum in terms of the target gene EF-1α when treated with F. asiaticum alone at 72 hpi was significantly higher than that when treated with NAD and a spore suspension of F. asiaticum. The relative expression levels of defence-related genes in strawberry roots treated with NAD at 72 hpi were determined. The genes NPR1 and PDF1 were markedly upregulated compared with other genes, suggesting that the expression of genes related to disease resistance was activated by NAD, resulting in disease resistance in strawberries. Our results provide theoretical support for the biological control of strawberry black root rot.